Design and Implementation of Website-Based Contract Management Information System - Fadlur Rahman Fa’iq; Elah Nurlelah; Taufiqurrochman (Jurnal Teknologi, 2026)
Kontrakan are a type of residential rental business often managed independently by property owners. The management process is frequently still done manually, such as recording tenant data, payment transactions, and room promotion, which risks data loss and recording errors. This research aims to design and implement a website-based boarding house management information system to assist owners in managing tenant data, payment transactions, recording and reporting expenses, and providing real-time information to prospective tenants. The system development method uses the waterfall model, which includes requirements analysis, design, implementation, testing, and maintenance. The system is developed with the Laravel framework and the MySQL database. The implementation results show that this system can increase operational efficiency, simplify recording and reporting, and provide convenience for tenants to access information and transaction history independently.